Examining the Pros and Cons of Using Game-based Learning for Vocabulary Instruction to Junior High School Students - Pardiansyah, Satria Ahmad; Muhtarom, Muhtarom; Gunairawati, Junaenik Latiefah (Department of English Language Education, UIN Sunan Ampel Surabaya, 2024)
Recent years have seen a considerable change within the educational environment, this is partly down to innovation in technology and teaching methods. Game-based learning (GBL) is one of the well-known approaches to include game elements in instructional processes to enhance student engagement and learning results. Based on the background above, this study focuses on investigating the advantages and disadvantages of GBL in teaching new vocabulary for seventh grade students at class VII-A of SMPN 25 Surabaya. The researcher conducted a qualitative descriptive study using an open-ended questionnaire to six students in the class for data collection to describe their perspectives. According to the results of the study, GBL provided an exciting and interesting atmosphere that gave rise to students' interest in learning English which referred to attention and comprehension. The investigation in question identified a number of problems, most notably those that pertained to technology limitations, for example device accessibility and internet connection issues, which can hinder the effectiveness of the GBL approach in the classroom.